The behavior of oaks in response to natural and induced exposure to the surfactant ABS - Moricca, S; Paoletti, E; Comparini, C (Ann. For. Sci., 1993)
Quercus pubescens, Q frainetto, Q ilex and Q robur were sprayed with ABS (sodium dodecyl benzenesulfonate, a surfactant often found in marine aerosols) over 2 growing seasons to test the effect of the surfactant on the leaf wax structure. Though all species were affected, they differed in their tolerance to ABS. The effect of ABS was also tested on the pollen quality of Q ilex. Pollen from declining and apparently healthy individuals was germinated in cultures with different concentrations of ABS. A negative effect on pollen germination and pollen tube length was noted. The reduction in pollen viability could affect the genetic resources of holm oak populations in the future.
Keywords: ABS; oak spp; pollen; wax structure